(untitled) (Baghdad Science Journal, 2025)
The objective of this study was shed light for cultivation and maintenance of Trichomonas vaginalis parasite growth after isolated it by vaginal swaps from females suffering vaginitis and abnormal vaginal discharges in these media CPLM and TAB media to detect growth curve, morphological changes and viability of parasite in the two culture media, together with effect of sheep and bovine serum on the growth of it. The results of this studies were showed there was abtaine differences between the two types of media , The maximum growth of parasite was in TAB medium after 72 hours incubation with use of bovine serum, while such growth was maximized after 144 hours incubation with the use of sheep serum. In CPLM medium, a maximum growth was reached after 120 hours incubation in the case of sheep serum, and 168 hours incubation in the case of bovine serum. After less than 24 hours incubation, the parasite grew exponentially in TAB medium, but such growth was associated with an increased rate of death in contrast, the reverse picture was observed in CPLM medium. Through the stages of growth, the parasite manifested different morphological changes, which were ranged from a non-motile spherical shape, nucleated and flagellated pear shape, binucleated and flagellated spherical shape, slow-moving large spherical shape and finally the a flagellated spherical shape (pseudocyst).